Impact of vereda dryness on the insect herbivore diversity in adjacent cerrado areas in Brazilian Protected Areas - Walter S. de Araújo; Luana T. Silveira; Luiz A. D. Falcão; Thallyta M. Vieira; Waldney P. Martins; Yule R. F. Nunes; Julio M. Grandez-Rios (Nature Conservation Research: Заповедная наука)
Unravelling the factors that influence plant-insect interactions remains a fundamental concern in terrestrial ecology. In the present study, we evaluated the impact of varying degrees of drying on cerrado areas adjacent to veredas on the species richness, abundance and composition of the insect herbivore fauna. Additionally, we examined differences in these impacts between various guilds (chewing and sucker insects) and developmental stages (adult and immature insects). The research has been performed in study areas located in three Protected Areas in Brazil. In total, we recorded 106 species of herbivorous insects across five orders (Coleoptera, Hemiptera, Hymenoptera, Lepidoptera, and Orthoptera). Hemiptera and Coleoptera stood out as the orders with the highest species diversity and individual numbers. Among the families, Cicadellidae and Curculionidae exhibited the highest richness in species and abundance of individuals. We found that richness of herbivorous insects was higher in wet zones (20.2 ± 6.5) of the veredas compared to dry zones (12.3 ± 7.5), as well as the abundance of herbivorous insects was higher in wet zones (49.4 ± 25.5) than in the dry zones (15.8 ± 7.9). Whithin insect guilds, the abundance of chewing insects was higher in wet zones (34.0 ± 13.6) than in dry zones (16.3 ± 14.8), but this difference was not observed for the diversity of sucking insects. Regarding developmental stage, immature insects exhibited higher species richness in wet zones (10.4 ± 5.0) compared to dry zones (5.3 ± 2.1), while adult insect diversity did not show differences between the studied zones. Furthermore, the species composition of herbivorous insects, various trophic guilds (chewers and suckers) and developmental stages (adults and immature insect) did not significantly differ among the zones studied within the veredas. According to our findings, herbivorous insects exhibit a preference for wet environments, which provide better conditions and higher-quality food resources for development and reproduction.